The Role of Tetrahydrobiopterin and Dihydrobiopterin in Ischemia/Reperfusion Injury When Given at Reperfusion - Qian Chen; Elizabeth Eun Jung Kim; Katrina Elio; Christopher Zambrano; Samuel Krass; Jane Chun-wen Teng; Helen Kay; Kerry-Anne Perkins; Sailesh Pershad; Sloane McGraw; Jeffrey Emrich; Jovan S. Adams; et al. (Advances in Pharmacological Sciences)
Reduced nitric oxide (NO) bioavailability and increased oxidative stress are major factors mediating ischemia/reperfusion (I/R) injury. Tetrahydrobiopterin (BH4) is an essential cofactor of endothelial NO synthase (eNOS) to produce NO, whereas dihydrobiopterin (BH2) can shift the eNOS product profile from NO to superoxide, which is further converted to hydrogen peroxide (H2O2) and cause I/R injury. The effects of BH4 and BH2 on oxidative stress and postreperfused cardiac functions were examined in ex vivo myocardial and in vivo femoral I (20 min)/R (45 min) models. In femoral I/R, BH4 increased NO and decreased H2O2 releases relative to saline control, and these effects correlated with improved postreperfused cardiac function. By contrast, BH2 decreased NO release relative to the saline control, but increased H2O2 release similar to the saline control, and these effects correlated with compromised postreperfused cardiac function. In conclusion, these results suggest that promoting eNOS coupling to produce NO and decrease H2O2 may be a key mechanism to restore postreperfused organ function during early reperfusion.